Default risks, moral hazard, and market-based solution: Evidence from renewable energy market in Bangladesh - Monzur Hossain; Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2019)
This paper analyzes a unique case of default risks and associated factors of a solar home system (SHS) program in Bangladesh and, within that context, proposes a theoretical market-based solution to finance a renewable energy (RE) program. The paper first develops a theoretical framework that highlights the problem of moral hazard in a subsidized government-sponsored program and then empirically assesses the default risks under the program. Using a primary survey data of 1,300 households, and applying probit and cox's proportional hazard model, we find that financial constraints, higher prices, natural disasters, and poor after-sales service are the factors that increase the probability of default, but in a different magnitude depending on the nature of customers. The factors that increase the probability of default for the group who are not willing to pay back (about 35% of total defaulters) are linked to adverse selection, perhaps due to moral hazard problems. The proposed market-based solution predicts that if the government uses a spillover revenue-based financing approach, it will increase the rate of return for private investors as well as the efficiency of RE programs.
Keywords: Q41; Q42; Q43; Q47; Q48; 330; Bangladesh; default risks; renewable energy; market-based solutions; solar homes; spillover tax revenue